Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Surface-reconstructed manganese oxides for enhanced external-oxidant-free degradation of bisphenol A: A direct electron transfer mechanism - Dawei Wang; Yihan Zhu; Keyi Gao; Zhuang Liu; Tong Li; Lin Chen; Yilan Jiang (Chemical Engineering Journal, 2026)

Comparative plastid genomics of five Ormosia species (fabaceae): insights into structural variation and morphological homoplasy - Shihong Zhang; Fengcheng Deng; Yixiong Zhao; Jiating Wang; Dipak Khadka; Jieyu Lin; Yuhua Hu; Keyi Fu; Lei Jiang; Mingxuan Zheng; Shi Shi (Plant Systematics and Evolution, 2026)

Coupling upconversion effect with p-n heterojunction on TiAl6V4 to eradicate bacterial biofilms - Keyi Yao; Lixuan Huang; Jie Shao; Junyu Dong; Junhua Xu; Yongsheng Liu; Sze Wing Cheung; Lin Xiang; Xuemei Zhou (Chemical Engineering Journal, 2026)

Pollutant control and material conversion of the waste graphite recovered from spent lithium-ion batteries: Preparation of building composite materials - Yusen Wu; Pengcheng Wang; Keyi Lin; Jiaqi Hu; Yonggao Fu; Jie Zhu; Jujun Ruan (Resources, Conservation and Recycling, 2026)

Sustainable thermal conversion of waste wind turbine blades: Environmental impact and pollutant footprint analysis - Jinnuo Dai; Keyi Lin; Chenjie Zhu; Yusen Wu; Jujun Ruan (Environmental Impact Assessment Review, 2025)

Al3+ driven-hydrolysis of amide group presented in the interface between EVA and glass for the decapsulation of waste photovoltaic laminates - Yusen Wu; Jiahua Lu; Keyi Lin; Jujun Ruan (Resources, Conservation and Recycling, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

From spent lithium-ion batteries to functional materials: A review - Tingjin Zhou; Keyi Lin; Yusen Wu; Baojia Qin; Jie Zhu; Zhe Huang; Zhenming Xu; Jujun Ruan (Resources, Conservation and Recycling, 2024)

Separation cathode materials from current collectors of spent lithium-ion battery through low-energy mechanical friction technology - Keyi Lin; Yusen Wu; Ying Shen; Yanrui Zheng; Zicheng Wang; Jinjuan Chen; Taoli Wu; Jie Zhu; Zhe Huang; Baojia Qin; Jujun Ruan (Resources, Conservation and Recycling, 2024)

High nutrient utilization and resorption efficiency promote bamboo expansion and invasion - Keyi Zuo; Lili Fan; Ziwu Guo; Le Zhang; Yiyang Duan; Jingrun Zhang; Shuanglin Chen; Hua Lin; Ruicai Hu (Journal of Environmental Management, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Attentional impairment and altered brain activity in healthcare workers after mild COVID-19 - Keyi Lin; Yaotian Gao; Wei Ji; Yan Li; Wei Wang; Mengcheng Du; Jia Liu; Zhengyu Hong; Tao Jiang; Yuyang Wang (Brain Imaging and Behavior, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is highly transmissible and pathogenic. Patients with mild cases account for the majority of those infected with coronavirus disease 2019 (COVID-19). Although there is evidence that many patients with COVID-19 have varying degrees of attentional impairment, little is known about how SARS-COV-2 affects attentional function. This study included a high-risk healthcare population divided into groups of healthcare workers (HCWs) with mild COVID-19 (patient group, n = 45) and matched healthy HCWs controls (HC group, n = 42), who completed general neuropsychological background tests and Attention Network Test (ANT), and underwent resting-state functional magnetic resonance imaging (rs-fMRI) using amplitude of low-frequency fluctuation (ALFF) to assess altered brain activity; Selective impairment occurred in orienting and executive control networks, but not in alert network, in the patient group, and widespread cognitive impairment encompassing general attention, memory, and executive dysfunction. Moreover, the patient group had significantly lower ALFF values in the left superior and left middle frontal gyri than the HC group. SARS-COV-2 infection may have led to reduced brain activity in the left superior and left middle frontal gyri, thus impairing attentional orienting and executive control networks, which may explain the development of attentional deficits after COVID-19.

Recovery of pure lead and preparation of nano-copper from waste glass diodes via a clean and efficient technology of step-by-step vacuum evaporation-condensation - Taiyu Huang; Keyi Lin; Xiao Tan; Jujun Ruan (Resources, Conservation and Recycling, 2023)

Discrimination of Tourette Syndrome Based on the Spatial Patterns of the Resting–State EEG Network - Keyi Duan; Qian Wu; Yuanyuan Liao; Yajing Si; Joyce Chelangat Bore; Fali Li; Qin Tao; Li Lin; Wei Lei; Xudong Hu; Dezhong Yao; Changfu Pei; et al. (Brain Topography, 2021)

Carboniferous integrative stratigraphy and timescale of China - Xiangdong Wang; Keyi Hu; Wenkun Qie; Qingyi Sheng; Bo Chen; Wei Lin; Le Yao; Qiulai Wang; Yuping Qi; Jitao Chen; Zhuoting Liao; Junjun Song (Science China Earth Sciences, 2019)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)